Implementación de un sistema de gestión ambiental en el manejo de residuos sólidos del proyecto de exploración Colquemayo – CIA de minas Buenaventura S.A.A - Villanueva Reátegui, Iván Carlos (2013)
The Colquemayo MiningExploration Project belong to Buenaventura Mines, is one ofthe projects of exploration that did not possess a System of Environmental Management for the Managing ofthe Salid waste. In the present investigation we will see the implementation of the Environmental Management System ISO 14001 applied to the salid waste management. According to the initial diagnosis there were improved the conditions of the area of work in the Salid Residues Managing, from his generation up to his temporary storage, and finally the final disposition. Por the classification and quantification ofthe Salid Waste we have used the techniques of qualification and quantification, where we find different characteristics of the sol id waste in terms of their dangerousness, between them we have the toxicity, flammability, explosiveness, etc. Within the quantification of the Salid Waste we have the months in which they were generated more waste and the months that generated less salid waste, at the same time what are the waste that is generated more. Quantif)¡jng helped us see what is the volume of waste generated in Colquemayo exploration project, the monthly average salid waste generation between January - April, TN was 1.6405, the highest percentage of waste generation were Organic waste, with a value of 53%, Hospital waste has a value <1 %, dueto the generation that was very little. Jt is implement the environmental management system in the Management of Sol id Waste, which is based on the environmental aspects that in this case the bad management of the Salid Waste can cause, taking the identification ofthese environmental aspects they were categorized in (03) groups, and according to these groups created the timetables of environmental management.